An Orc6 tether mediates ORC binding-site switching during replication origin licensing - David Driscoll; Larry J. Friedman; Jeff Gelles; Stephen P. Bell (Proceedings of the National Academy of Sciences, 2025)
During origin licensing, the origin recognition complex (ORC) loads two Mcm2-7 helicases onto DNA in a head-to-head conformation, establishing the foundation for subsequent bidirectional replication. Single-molecule experiments support a helicase-loading model in which one ORC loads both Mcm2-7 helicases at origins. For this to occur, ORC must release from its initial Mcm2-7 and DNA binding sites, flip over the helicase, and bind the opposite end of the Mcm2-7 complex and adjacent DNA to form the MO complex. Importantly, this binding-site transition occurs without ORC releasing into solution. Using a single-molecule FRET assay, we show that the N-terminal half of Orc6 tethers ORC to the N-terminal region of Mcm2 during ORC’s binding-site transition. This interaction involves both the folded Orc6 N-terminal domain (Orc6N) and the adjacent unstructured linker and forms before ORC releases from its initial Mcm2-7 interaction. The absence of this interaction increases the rate of ORC release into solution, consistent with a tethering function. CDK phosphorylation of ORC inhibits the tethering interaction, providing a mechanism for the known CDK inhibition of MO complex formation. Interestingly, we identify mutations in the Orc6 linker region that support MO complex formation but prevent double-hexamer formation by inhibiting stable second Mcm2-7 recruitment. Our study provides a molecular explanation for a one-ORC mechanism of helicase loading and demonstrates that Orc6 is involved in multiple stages of origin licensing.